2012
DOI: 10.1097/iae.0b013e31821f5d81
|View full text |Cite
|
Sign up to set email alerts
|

Macular Hole After Vitrectomy for Primary Rhegmatogenous Retinal Detachment

Abstract: Macular hole may develop after pars plana vitrectomy for RRD, and these cases can be surgically repaired. The pathogenesis of the formation of these holes remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 30 publications
1
26
2
2
Order By: Relevance
“…15, 16 This includes cases of scleral buckle and pneumatic retinopexy procedures for retinal re-attachment (Table 4). 1525 Clinical characteristics and outcomes from the current study were compared with published data. In the current study, 67% of patients were younger than 65 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…15, 16 This includes cases of scleral buckle and pneumatic retinopexy procedures for retinal re-attachment (Table 4). 1525 Clinical characteristics and outcomes from the current study were compared with published data. In the current study, 67% of patients were younger than 65 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] The underlying cause as suggested by Gass is a progressive anteroposterior and/or tangential traction in the premacular vitreous cortex. 16 Recently, glial cells and myofibroblasts have been suggested to contribute to the generation of such traction forces in the vitreous body, and Schumann et al 17 reported that in 57% of the cases such cell proliferation was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the case reports and case series, the waiting period varies from a few weeks to 6 months [1, 71,72]. A close observation with periodic OCT reevaluation is probably safe and justified at least for 1-2 months, particularly for small macular holes (approximately 200 mm) and in presence of good vision (>20/50), irrespective of the cause [73]. Presence of afferent pupillary defect with traumatic macular hole also justifies initial observation to ascertain the contribution of optic neuropathy to visual loss.…”
Section: Surgical Modificationsmentioning
confidence: 99%